Do Gross and Fine Motor Skills Differentially Contribute to Language Outcomes? A Systematic Review - Gonzalez, Sandy L.; Alvarez, Veronica; Nelson, Eliza L. (Frontiers in Psychology, 2019)
Background: Changes in motor development provide children with new learning opportunities to interact with objects, their environment, and with caregivers. Previous research finds that both gross and fine motor skills are predictive of later language outcomes across early infancy and childhood. However, gross and fine motor skills afford different types of interactions. Thus, gross and fine motor skills may potentially differ in the developmental trajectories through which cascading changes in language may occur. The aim of the present study was to investigate whether there are differences in the predictive capacities of gross and fine motor skills towards language outcomes across infancy and early childhood in typical development. Method: A systematic review of existing literature on motor-language cascades was conducted across studies measuring gross and/or fine motor and language development in children from 0 to 5 years old. Searches were conducted in PsycINFO, PubMed, and MEDLINE. Keywords used were a combination of “gross motor”, “fine motor”, “motor performance”, “motor development”, or “psychomotor development” along with “language”, “language development”, or “communication skills”. Two independent reviewers screened abstracts and full texts based on inclusion and exclusion criteria. Results: A total of 23 articles were retained. Of these, seven studies measured only gross motor skills, four studies measured only fine motor skills, and 12 studies measured both gross and fine motor skills in the same study. Studies used a variety of measures to assess gross motor skills, fine motor skills, and language development (e.g., parent report, in lab observations, standardized assessment), and findings varied based on analyses used. Results demonstrated that both gross and fine motor skills are related to language outcomes, but due to a smaller amount of studies testing fine motor skills, conclusions regarding whether one is more important for language outcomes cannot be drawn. Conclusions: We conclude that both gross and fine motor skills help foster language development from infancy to early childhood. Limitations regarding current knowledge regarding the mechanisms that underlie motor-language cascades are discussed, as well as the need for more studies on fine motor skills.